Soil infiltration, runoff and sediment yield from a shallow soil with varied stone cover and intensity of rain - Mandal, U.K; Rao, K.V; Mishra, P.K; Vittal, K.P.R; Sharma, K.L; Narsimlu, B; Venkanna, K (European journal of soil science, 2005)
Summary Stones on the surface of the soil enhance infiltration and protect the soil against erosion. They are often removed in modern mechanized agriculture, with unfortunate side‐effects. We evaluated experimentally the influence of surface stones on infiltration, runoff and erosion under field conditions using a portable rainfall simulator on bare natural soil in semi‐arid tropical India, because modernization and mechanization often lead to removal of these stones in this region. Four fields with varied cover of stones from 3 to 65% were exposed to three rainfall intensities (48.5, 89.2 and 136.8 mm hour−1). Surface stones retarded surface runoff, increased final infiltration rates, and diminished sediment concentration and soil loss. The final infiltration ranged from 26 to 83% of rainfall when the rainfall intensity was 136.8 mm hour−1. The reduction in runoff and soil erosion and increase in infiltration were more pronounced where stones rested on the soil surface than where they were buried in the surface layer. The sediment yield increased from 2 g l−1 for 64.7% stone cover with rainfall of 48.5 mm hour−1 to 70 g l−1 for 3.5% stone cover with rain falling at 136.8 mm hour−1. The soil loss rate was less than 2 t ha−1 hour−1 for the field with stone cover of 64.7% even when the rainfall intensity was increased to 136.8 mm hour−1. The effects of stones on soil loss under the varied rainfall intensities were expressed mathematically. The particles in the sediment that ran off were mostly of silt size.